Karakoram Ka Taj Mehal - "Ahmad, Namrah" (Lahore; Ilmo Irfan Publisher, 2019)
Nice novel with different theme. It's a kind of itinerary, based on upper side of Pakistan and mountains of Rakaposhi, Karakoram.
Keywords: Urdu Novel